Evaluation of combat effectiveness of unmanned aerial vehicle group in uncertain situations - SUN Pengyao, HUANG Yanyan, WANG Kaisheng, WU Kui (Zhihui kongzhi yu fangzhen)
A set of unmanned aerial vehicle (UAV) swarm combat effectiveness evaluation methods based on combat process simulation is constructed to address the issue of UAV swarm combat effectiveness evaluation in uncertain situations. Firstly, analyze the operational process of unmanned aerial vehicle (UAV) reconnaissance and strike missions from the perspective of closed-loop combat environment. Secondly, design a combat method calculation module based on the various steps of the closed-loop combat environment, and combine the designed parameter setting module, battlefield situation generation and recording module, global progress controller, and combat data recording module to form a complete simulation system for unmanned aerial vehicle group observation and combat process. Then, based on the available simulation data of the combat process, construct core effectiveness indicators and auxiliary effectiveness indicators, and provide a calculation and coupling method for each indicator. Finally, a scenario is set up to simulate the combat process of unmanned aerial vehicle swarms using different deployment schemes, evaluate and analyze the combat effectiveness, verify the feasibility of the proposed method, and achieve effective evaluation of the combat effectiveness of unmanned aerial vehicle swarms under uncertain situations.